2022
DOI: 10.1038/s12276-022-00843-8
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory marker protein regulation of glucagon secretion in hyperglycemia

Abstract: The olfactory marker protein (OMP), which is also expressed in nonolfactory tissues, plays a role in regulating the kinetics and termination of olfactory transduction. Thus, we hypothesized that OMP may play a similar role in modulating the secretion of hormones involved in Ca2+ and cAMP signaling, such as glucagon. In the present study, we confirmed nonolfactory α-cell-specific OMP expression in human and mouse pancreatic islets as well as in the murine α-cell line αTC1.9. Glucagon and OMP expression increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Along these lines, new α-cell targets are continuing to be identified which have potential for small molecule interventions. Recent work showed the olfactory marker protein ( Omp ) regulates cAMP in α-cells and affects AMP kinase activity ( 34 ). α-cell-specific Omp knockout mice have reduced baseline AMPK phosphorylation and knockdown of Omp in an α-cell line caused a loss of glucose-induced reduction in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, new α-cell targets are continuing to be identified which have potential for small molecule interventions. Recent work showed the olfactory marker protein ( Omp ) regulates cAMP in α-cells and affects AMP kinase activity ( 34 ). α-cell-specific Omp knockout mice have reduced baseline AMPK phosphorylation and knockdown of Omp in an α-cell line caused a loss of glucose-induced reduction in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was demonstrated that ectopic odorant receptors (ORs) in pancreatic islets regulate insulin and glucagon secretion, fatty acid oxidation, lipogenesis, thermogenesis, and other processes. At least 47 ORs have been proven to be expressed in human pancreatic islets and the pancreatic β-cell line MIN6 [162], where these receptors regulate insulin secretion and inflammation [163][164][165][166][167]. The olfactory marker protein (OMP) is also expressed in pancreatic islets, especially in α-cells, in which it participates in glucagon secretion regulation.…”
Section: Taar1 Co-expression Cluster Changes In Metabolic Diseasesmentioning
confidence: 99%